Fabrication and characterisation of Silicon-Germanium Schottky diode - Tan, Oscar Aik Poh. (2008)
In this project, both the silicon and silicon germanium schottky barrier diode were fabricated and studied. Pt, Ti and W metal were investigated as schottky materials. Pt/n-Si, Ti/n-Si, W/n-Si, Pt/p-Si, Ti/p-Si and W/p-Si schottky diodes were fabricated and found to give good quality schottky diode performance with suitable fine-tuning of the fabrication process to reduce over-alloying.